The Effect of Carbofuran and Endosulfan on the African Catfish, Clarias Garieplnus - Mohamed Elamin Abu Zeid, Isam Eldin (2001)
This study was undertaken to determine the toxic effects of sub-lethal concentrations of carbofuran and endosulfan on some behavioural, morphological, biaccumulation, biochemical, histopathological, and molecular aspects of the freshwater African catfish, Clarias gariepinus. The toxicity of carbofuran and endsulfan was ascertained by estimating the LC₅₀. The calculated 96-h LC₅₀ values of carbofuran and endosulfan for juveniles of Clarias gariepinus were found to be 10.4 p.p.m and 2l.6 p.p.b respectively, under tropical condition. The test fish swam erratically, struggled to breath, often swam to the surface, followed by loss of equilibrium. The color of the skin became progressively pale during the period of the test, The liver glutamate oxaloacetate transaminase (GOT), glutamate pyruvate transaminase (GPT) and acetycholinesterase (AchE) were determined photometrically. Within 16 days of treatment, the activity levels of GOT and GPT were significantly (p<0.05, p<0.01, p<0.001) increased by 203% and 121% for carbofuran and 167% and 195% for endosulfan respectively, whereas, AchE activity levels were inhibited following exposure to the test pesticides. With no exceptions, the in vivo and in vitro effects of carbofuran and enosulfan on GOT, GPT and AchE were qualitatively similar. The pesticide concentration in the tissues was in the order of liver> intestine> gill> brain> muscle. The highest concentration of the test pesticides (353.47 µg/g carbofuran and 1409.35 µg/g endosulfan) were found in the liver 24 hours after treatment. Liver lesions were observed following exposure to both pesticides. The evidence of pesticide accumulation was elucidated by necrosis and damaged fish liver. The depletion in the protein content was observed following exposure to carbofuran and endosulfan. The RNA concentrations were significantly decreased in Clarias gariepinus exposed to both pesticides, whereas, DNA concentrations tend to remain constant. The DNA molecular weight of the control fish was found to be about 16832 bp, whereas, the DNA molecular weights of carbofuran and endosulfan exposed fish were 14505 and 14505 bp respectively. The liversomatic index decreased to 2.11 for carbofuran and 1.59 for endosulfan in comparison to control. The biochemical, molecular, bioaccumulation, histological, behavioural and morphological techniques employed in this study may be used to detect and assess any pesticidal pollution in the aquatic environment at an early stage of pollution.